Development of free legal aid system in Ukraine - Rohatynska, Nina (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article analyzes the activity of free legal aid in Ukraine, the mechanism for implementing this right, the grounds, procedure and state guarantees for the provision of free legal aid. The task of the Coordination Center is defined. The shortcomings of the system of free legal aid are presented.